GnRH-a-Induced Perimenopausal Rat Modeling and Black Cohosh Preparations’ Effect on Rat’s Reproductive Endocrine - Chen, Jiming; Wang, Huihui; Dong, Zhiyong; Liu, Junling; Qin, Zhenyue; Bao, Mingyue; Yu, Hongxia; Zhang, Shoufeng; Zhang, Wendi; Qi, Chunjian; Wu, Jie (Frontiers in Endocrinology, 2021)
Background Endometriosis (EMS) is an estrogen-dependent disease, which easily recurs after operation. Gonadotropin-releasing hormone agonist (GnRH-a), an estrogen-inhibiting drug, can effectively inhibit the secretion of gonadotropin by pituitary gland, so as to significantly decrease the ovarian hormone level and facilitate the atrophy of ectopic endometrium, playing a positive role in preventing postoperative recurrence. The application of GnRH-a can lead to the secondary low estrogen symptoms, namely the perimenopausal symptoms, and is a main reason for patients to give up further treatment. The add-back therapy based on sex hormones can well address the perimenopausal symptoms, but long-term use of hormones may cause the recurrence of EMS, as well as liver function damage, venous embolism, breast cancer and other risks, which has long been a heated topic in the industry. Therefore, it is necessary to find effective and safe anti-additive drugs soon. Studies at home and abroad show that, as a plant extract, isopropanolic extract of cimicifuga racemosa (ICR) can well relieve the perimenopausal symptoms caused by natural menopause. Some studies have preliminarily confirmed that black cohosh preparations can antagonize perimenopausal symptoms of EMS patients treated with GnRH-a after operation. Objective To establish a rat model of perimenopausal symptoms induced by GnRH-a injection, for the purposes of laying a foundation for further research and preliminarily exploring the effect of black cohosh preparations on reproductive endocrine of the rat model. Method The rat model of perimenopausal symptoms was established by GnRH-a injection, and normal saline (NS injection) was used as the control. The rats were randomly divided into four groups according to different modeling methods and drug intervention schemes. GnRH-a injection + normal saline intervention group (GnRH-a + NS), normal saline injection control + normal saline intervention group (NS + NS), GnRH-a injection + estradiol intervention group (GnRH-a + E2), and GnRH-a injection + black cohosh preparations intervention group (GnRH-a + ICR). After modelling was assessed to be successful with the vaginal smear method, the corresponding drugs were given for intervention for 28d. In the process of rat modeling and drug intervention, the skin temperature and anus temperature of the rat tails were measured every other day, the body weights of the rats were measured every other day, and the dosage was adjusted according to the body weight. After the intervention was over, the serum sex hormone level, the uterine weight, the uterine index, and the endometrial histomorphology changes, as well as the ovarian weight, the ovarian index, and the morphological changes of ovarian tissues of each group were measured. Results (1) The vaginal cell smears of the control group (NS + NS) showed estrous cycle changes, while other model rats had no estrous cycle of vaginal cells. (2) The body weight gains of the GnRH-a + NS, GnRH-a + E2 and GnRH-a + ICR groups were significantly higher than that of the NS + NS control group. The intervention with E2 and ICR could delay the weight gain trend of rats induced by GnRH-A. (3) After GnRH-a injection, the temperature of the tail and anus of rats showed an overall upward trend, and the intervention with E2 and ICR could effectively improve such temperature change. (4) The E2, FSH, and LH levels in the GnRH-a + NS, GnRH-a + E2, and GnRH-a + ICR groups were significantly lower than those in the NS + NS group (P < 0.01). The E2 level was significantly higher and the LH level was significantly lower in the GnRH-a + E2 group than those in the GnRH-a + NS and GnRH-a + ICR groups (P < 0.05). Compared with those of the GnRH-a + NS and GnRH-a + ICR groups, the FSH level of the GnRH-a + E2 group showed a slight downward trend, but the difference was not statistically significant (P > 0.05). There was no significant difference in the levels of sex hormones between the GnRH-a + NS group and GnRH-a + ICR group (P > 0.05). (5) Compared with those of the NS + NS group, the uterine weight and uterine index of the GnRH-a + NS, GnRH-a + E2 and GnRH-a + ICR groups significantly decreased (P < 0.01). In a comparison between the groups, the uterine weight and uterine index in the GnRH-a + NS and GnRH-a + ICR groups were significantly lower than those in the GnRH-a + E2 group (P < 0.01). There was a statistical difference in the uterine weight and uterine index between the GnRH-a + NS group and GnRH-a + ICR group (P > 0.05). (6) Compared with those of the NS + NS group, the ovarian weight and ovarian index of the GnRH-a + NS, GnRH-a + E2 and GnRH-a + ICR groups significantly decreased (P < 0.01). There was no statistical difference in the ovarian weight and ovarian index among the GnRH-a + E2, GnRH-a + NS and GnRH-a + ICR groups (P > 0.05). (7) Compared with those in the NS + NS group, the number of primordial follicles increased significantly, while the number of growing follicles and mature follicles decreased significantly in the GnRH-a + NS, GnRH-a + E2, and GnRH-a + ICR groups (P < 0.01), but there was a statistical difference in the total number of follicles among the four groups (P > 0.05). Conclusions The GnRH-a injection could achieve the desired effect. The animal model successfully achieved a significant decrease in the E2, FSH, and LH levels in rats, and could cause the rats to have rising body surface temperature similar to hot flashes in the perimenopausal period. The intervention with E2 and ICR could effectively relieve such “perimenopausal symptoms”, and ICR had no obvious effect on the serum sex hormone level in rats.